Supporting Teaching and Research in an Online Environment: Developing the University of London Library Model - Chambers, Sally (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Founded in 1837, the University of London Library (ULL) is the central research library of the University of London with particular research strengths across the broader arts, humanities and social sciences. With the development of information and communications technology, it has become a hybrid library, offering access to electronic collections but also extending access to services and its physical collections through its website and online catalogue. Research libraries now face the challenge of supporting distance learning. The ULL has risen to this challenge by being a partner in the development of webenhanced distance learning by the University of London External Programme’s Virtual Campus Project. To do this, the ULL has initiated the Virtual Library Service (VLS) Project. Within the research-focussed University of London, the ULL has anticipated the potential research-support needs of its students. It is also leading a separately funded Virtual Research Environment (VRE) Project on behalf of the University Libraries Committee to address these needs and inform the University of London’s activities in the virtual sphere. The University of London has created the Electronic Library Projects Team (ELPT) to undertake the VLS and VRE projects and ensure that they develop along complementary lines. This paper outlines how the ULL is supporting teaching and research in an online environment through the development of its VLS and VRE models.